REPRODUCTIVE CHANGES IN WOMEN WITH PREMATURE OVARIAN FAILURE - Boboxonova Muhayyoxon Mo‘minjonovna (Journal of Medical Genetics and Clinical Biology, 2024)
Failure to become pregnant after therapy forces the patient to use assisted reproductive technologies using donor embryos and oocytes, while the effectiveness of in vitro fertilization does not exceed 58%. To prevent this outcome, if a woman has risk factors for developing premature ovarian failure, it is necessary to timely assess the ovarian reserve with the preservation of her own oocytes for subsequent assisted reproductive technologies.